Physical activity assessment and prescription for overweight patients in primary care in Portugal: A quality improvement project - Rita Vale Lima; Carina Antunes; Filipa Ribeiro; Andreia Teixeira; Carlos Martins (Preventive Medicine Reports, 2025)
Objective: Regular physical activity is a protective factor against chronic diseases. Globally, there is a trend of increasing physical inactivity, which contributes to rising rates of overweight. Recognising this issue, primary healthcare plays a crucial role in promoting healthy lifestyles. This study aimed to improve the screening and prescription of physical activity by utilising the assessment tool available in the SClínico® (Primary Care Clinical System) and the counselling tool in the PEM® software (Electronic Medical Prescription). Methods: This experimental, longitudinal quality improvement study was conducted at a Family Health Unit in Portugal from July 2023 to January 2024. It included patients aged 18 or older who were classified as overweight (body mass index [BMI] 25–29.9 kg/m2). A simple random sample (n = 357) was selected. The initial assessment took place in July 2023, followed by the establishment of quality standards and an educational intervention. The follow-up assessment was conducted in January 2024. Results: During the initial evaluation, the assessment tool was completed for 44 patients; however, none completed the counselling tool. These findings were reported at a team meeting, where corrective actions were proposed. In the second evaluation, the assessment tool was completed for 134 patients, and the counselling tool for 19. Conclusions: The implementation of physical activity assessment and counselling tools has increased notably. This highlights the importance of monitoring programs and training health professionals to provide brief advice for promoting physical activity. Further improvements may be achieved through additional corrective measures, larger samples, and extended follow-up periods.